Influence of 3-Hydroxyflavone on Colloidal Stability and Internationalization of Ag Nanomaterials Into THP-1 Macrophages. Issue 3 (23rd July 2019) - Liang, Yongqi; Xie, Min; Li, Juan; Liu, Liangliang; Cao, Yi
Polyphenols as typical food components can influence the colloidal properties and internalization of nanomaterials (NMs) into mammalian cells. Recently, we found that 3-hydroxyflavone (H3) promoted intracellular Zn ions in ZnO nanoparticle (NP) exposed Caco-2 and HepG2 cells. However, it is unclear if H3 could affect the internalization of metal-based NMs with different morphologies. This study investigated the influence of H3 on colloidal aspects of Ag NPs and Ag nanoflakes (NFs) as well as the internalization of Ag NMs into THP-1 macrophages. 3-Hydroxyflavone at 50 μM promoted the solubility and altered hydrodynamic size, polydispersity index, and ζ potential of Ag NPs and Ag NFs, which indicated that H3 could affect the colloidal stability of Ag NMs. Only H3 but not Ag NMs significantly decreased mitochondrial activities of THP-1 macrophages. The internalization of Ag NMs was markedly increased due to the presence of H3. 3-Hydroxyflavone also exhibited antioxidative properties as it reduced intracellular reactive oxygen species and promoted the activities of ABC transporters as it reduced retention of Calcein in Ag NM-exposed THP-1 macrophages. We concluded that H3 promoted the internalization of Ag NMs into macrophages probably by altering the colloidal stability of Ag NMs and consequently NM-macrophage interactions.